2004
DOI: 10.1038/sj.cgt.7700709
|View full text |Cite
|
Sign up to set email alerts
|

Route of administration influences the antitumor effects of bone marrow-derived dendritic cells engineered to produce interleukin-12 in a metastatic mouse prostate cancer model

Abstract: Gene-modified dendritic cells (DC) provide unique therapeutic strategies for prostate cancer; however, the comparative evaluation of specific delivery options using appropriate preclinical models has not been described. In this study, bone marrow-derived DC were genetically engineered to express high levels of interleukin-12 (IL-12) with or without the costimulatory molecule B7-1, by ex vivo infection with recombinant adenoviral vectors. We used an orthotopic metastatic mouse prostate cancer preclinical model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 27 publications
(27 reference statements)
1
26
0
Order By: Relevance
“…19 Cells were grown as previously described. 18,[20][21][22] The replication-defective adenoviral vector expressing RTVP-1 (AdRTVP-1) and a control adenoviral vector containing the b-galactosidase gene (Adbgal) were prepared as described, 18 and viral concentration was expressed as plaque-forming units. Western blotting with affinity-purified antibody to RTVP-1 was as described.…”
Section: Cells and Adenoviral Vectorsmentioning
confidence: 99%
“…19 Cells were grown as previously described. 18,[20][21][22] The replication-defective adenoviral vector expressing RTVP-1 (AdRTVP-1) and a control adenoviral vector containing the b-galactosidase gene (Adbgal) were prepared as described, 18 and viral concentration was expressed as plaque-forming units. Western blotting with affinity-purified antibody to RTVP-1 was as described.…”
Section: Cells and Adenoviral Vectorsmentioning
confidence: 99%
“…The adjuvant administration of IL-12 after immunization with a vaccinia virus expressing the co-stimulatory molecule B7-1 to tumor-bearing mice similarly enhanced animal survival [106]. Other recent approaches include the co-administration of IL-12 along with tumor antigen-pulsed DC [107] and the engineering of tumor cells or antigen-pulsed DC to express IL-12 alone [108,109] or in combination with IL-18 [66] for enhanced anti-tumor immunity. In humans, many studies have combined IL-12 with peptide vaccines for the improved treatment of cancers.…”
Section: Conclusion and Expert Opinionmentioning
confidence: 99%
“…[18][19][20] The construction and purification of the adenoviral vectors AdIl-12, AdIL-12/ B7 and Adbgal have been described. [16][17][18][19]21 Mice Male 129/Sv mice were used at 12-16 weeks of age.…”
Section: Cells and Adenoviral Vectorsmentioning
confidence: 99%
“…To this end we have shown that antitumor and antimetastatic prostate cancer therapy can also be initiated with AdIL-12-modified macrophage 18 or dendritic cells 19 injected directly into mouse prostate orthotopic tumors. We undertook the present studies to evaluate if the systemic activities generated following orthotopic delivery of AdIL-12 were transferable via immune cells contained in the spleen of treated animals.…”
Section: Introductionmentioning
confidence: 99%